ARCHIVAL PROMOTION PRACTICES ON SOCIAL MEDIA: A CONTENT ANALYSIS OF THE UNIVERSITY OF INDONESIA ARCHIVES’ INSTAGRAM - Nadya Mentari; Tamara Adriani Salim (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
This study examines archival promotion practices through the Instagram account of the University of Indonesia Archives (@arsipui) within the framework of institutional digital communication. It analyzes the types of information shared, variations in content categories and formats, and user engagement. A descriptive quantitative approach was employed using content analysis of all posts up to June 10, 2025, collected through an Instagram Scraper, categorized into seven content types, and analyzed using Microsoft Excel. User engagement was measured using median values of likes and comments to account for the skewed distribution of social media data. The findings show that among 304 posts, video (135) and carousel formats (128) dominate compared to single-image posts (41). The most prominent categories are Archival Information and News (109 posts) and Archival Activities (73 posts), both of which generate the highest levels of engagement. Analytically, the results indicate that user engagement is not determined solely by content type, but by the interaction between content categories, visual formats, and platform distribution mechanisms.This study contributes by proposing a simplified conceptual framework in which user engagement is understood as the outcome of the interplay between content, format, and platform logic in archival digital communication. The findings suggest that archival promotion strategies should move beyond information-centered approaches toward more audience-oriented and visually narrative communication to enhance engagement in social media environments.